Solution-Processed Heterojunction Photodiodes Based on WSe2 Nanosheet Networks - Coleman, Jonathan; Carey, Tian (My University, 2023)
Solution-processed photodetectors incorporating liquid-phase-exfoliatedtransition metal dichalcogenide nanosheets are widely reported. However,previous studies mainly focus on the fabrication of photoconductors, ratherthan photodiodes which tend to be based on heterojunctions and are harderto fabricate. Especially, there are rare reports on introducing commonly usedtransport layers into heterojunctions based on nanosheet networks. In thisstudy, a reliable solution-processing method is reported to fabricateheterojunction diodes with tungsten selenide (WSe2) nanosheets as theoptical absorbing material and PEDOT: PSS and ZnO asinjection/transport-layer materials. By varying the transport layercombinations, the obtained heterojunctions show rectification ratios of up to≈104at±1 V in the dark, without relying on heavily doped silicon substrates.Upon illumination, the heterojunction can be operated in bothphotoconductor and photodiode modes and displays self-powered behaviorsat zero bias.
PUBLISHED
cited By 0
Keywords: nanosheet networks; heterojunction diodes; 2D materials; Photodetectors; Solution processed heterojunctions; Transition metal dichalcogenides